IMPROVEMENT OF THE TECHNOLOGY FOR CLEANING NATURAL GAS FUEL BURNING IN THERMAL POWER PLANTS - Soliyev Bobonazar Gulomjon ugli (Galaxy International Interdisciplinary Research Journal, 2023)
The efficiency of thermal power plants that use natural gas as fuel can be maximized and environmental pollution reduced through the use of appropriate cleaning technology. Innovations such as precision filtration, advanced chemical treatments, and sophisticated scrubbing techniques have made it possible to remove impurities and contaminants from natural gas fuel. This not only contributes to a cleaner and more sustainable energy future but also prolongs the lifespan of power-generation equipment by minimizing wear and tear caused by contamination.